1997
DOI: 10.1002/(sici)1098-2744(199707)19:2<74::aid-mc2>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Induction of p21/WAF1 and G1 cell-cycle arrest by the chemopreventive agent apigenin

Abstract: Apigenin is a plant flavonoid that has been shown to significantly inhibit ultraviolet-induced mouse skin tumorigenesis when applied topically and may be an alternative sunscreen agent for humans. A long-term goal of our laboratory is to elucidate the molecular mechanism or mechanism by which apigenin inhibits skin tumorigenesis. In a previous publication, we characterized the mechanism by which apigenin induced G2/M arrest in keratinocytes. More recent studies in our laboratory have provided evidence that api… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
2
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(83 citation statements)
references
References 27 publications
7
70
2
1
Order By: Relevance
“…Fifth, evidence for a role of the Ras 3 Raf 3 MEK 3 ERK pathway in the regulation of the cell cycle was provided by the use of apigenin, a plant flavonoid. In Ras-transformed cells, apigenin reverses the transformed phenotype, diminishes ERK activity and expression of the oncogenes c-fos and c-jun (33), and arrests the cell cycle at the G 0 -G 1 interface (31). Apigenin also inhibited the activity of CDK2 kinase and increased the levels of hypophosphorylated Rb in human diploid fibroblasts (31).…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, evidence for a role of the Ras 3 Raf 3 MEK 3 ERK pathway in the regulation of the cell cycle was provided by the use of apigenin, a plant flavonoid. In Ras-transformed cells, apigenin reverses the transformed phenotype, diminishes ERK activity and expression of the oncogenes c-fos and c-jun (33), and arrests the cell cycle at the G 0 -G 1 interface (31). Apigenin also inhibited the activity of CDK2 kinase and increased the levels of hypophosphorylated Rb in human diploid fibroblasts (31).…”
Section: Discussionmentioning
confidence: 99%
“…Topical application of apigenin has been shown to inhibit UV-mediated induction of ornithine decarboxylase activity, reduce tumor incidence and increase tumor-free survival in mice. Several other studies have provided evidence that apigenin prevents UV-induced skin tumorigenesis by inhibiting the cell cycle and cyclin-dependent kinases (51). Exposure of mouse keratinocytes to apigenin induced G2/M cell cycle arrest and accumulation of the p53 tumor suppressor protein with increased expression of p21/WAF1.…”
Section: Apigenin and Leukemiamentioning
confidence: 95%
“…It has been shown that exposure of a wide array of malignant cells, including epidermal cells and fibroblasts to apigenin induces a reversible G2/M and G0/G1 arrest by inhibiting p34 (cdc2) kinase activity, accompanied by increased p53 protein stability (50,51). Apigenin has also been shown to induce WAF1/p21 levels resulting in cell cycle arrest and apoptosis in androgen-responsive human prostate cancer, LNCaP cells and androgen-refractory DU145 cells, regardless of the Rb status and p53-dependence or p53 independence (52,53).…”
Section: Achillea Millefoliummentioning
confidence: 99%
“…According to recent advances in the interpretation of events that occur during programmed cell death, the generation and spreading of ROS within the cell are consequences of the increased permeability of the mitochondrial membrane [80,109]. Lepley and Pelling [57] during a novel cell culture study with apigenin (a quercetin derivative), obtained evidence that flavonoid antioxidants may enhance apoptosis in certain tumor cell lines. Hydrogen peroxide (H 2 O 2 ), similarly to quercetin has been reported to stimulate the activity of the mitogen-activated protein kinases (MAPKs) ERK and JNK, and the expression of the proto-oncogenes c-fos and c-jun [97].…”
Section: Pufa As Ligands Of Transcription Factorsmentioning
confidence: 99%